How fear drives us apart: explaining the relationship between terrorism and social trust - Godefroidt, Amélie; Langer, Arnim (Terrorism and political violence, 2020)
A central aim of terrorism is to drive people apart and destroy social trust. Still, there is little empirical research which has systematically investigated the relationship between terrorist attacks, fear of terrorism, and social trust. In addition, the impact of terrorism is usually assumed to be uniform across different individuals and societies. In order to investigate the impact of terrorism as well as the fear of future terrorism on trust levels of different types of individuals and societies, we combine individual-level survey data of the most recent World Values Survey (WVS, Round 6, 2010-2014) with several indicators at the country-level. Our findings show that social trust is principally damaged by the fear of future terrorist attacks, more so than by past terrorist attacks. Moreover, this deleterious impact of the fear of terrorism on social trust is most prevalent in more democratic countries and among individuals who are more frequently exposed to television news. Hence, with relatively limited capabilities and resources, terrorists may therefore evoke disproportionate fear effects within democratic societies which are, at least partially, fueled by media exposure.